SEROLOGICAL DETECTION OF APPLE STEM GROOVING VIRUS PREVALENT IN DRY TEMPERATE ZONE OF HIMACHAL PRADESH (Journal of Plant Disease Sciences, 2017)
Horticultural crops being intensive  play an important role in countries' economy  through employment generation and  improving farm income. Among different  temperate fruits, apple ( x Malus domestica Borkh.) is the most important crop of the  world and is cultivated on an area of  5,051,851 ha with an annual production and  productivity of 84,630,275 T and 16.75  MT/ha, respectively (FAO, 2014). India ranks  5 in production of apple in the world with an th area of about 3,13,040 ha and an annual  production and productivity of 2497,680 MT  and 7.97 MT/ha respectively (FAO, 2014). In  Himachal Pradesh apple is being cultivated  over 1,10,679 ha with annual production of  7,77,126 MT (Annoymous, 2016). Whereas,  in dry temperate zone of Himachal Pradesh  apple is cultivated over 12,506 ha with an  a n n u a l p r o d u c t i o n o f 5 9 , 4 7 3 M T  (Annonymous, 2015). Though, cultivation of  apple has revolutionized the socio-economic  status of farmers of tribes of Himachal  Pradesh, yet the productivity of apple is very  low 4.76 MT/ha (Anonymous, 2015) is  relatively low in comparison to global  productivity of 16.75 MT/ha. Different  factors are responsible for low productivity of  apple, among these diseases play an important  role. Apple crop falls prey to wide range of  fungal, bacterial and viral pathogens, where,  viral diseases need greater attention for being  its systemic nature that passes to the  successive generations through clonal  propagation, thus causing decline of trees.  Latent viral infection goes unnoticed and  gradually results in the loss of plant vigour,  reduction in quality of produce as well as yield  of the crop.
Keywords: dry temperate zone, DAC-ELISA, ASGV